CATEGORICAL ANALYSIS OF STUDENT ENTHUSIASM RELATED TO THE 2024 INDONESIAN ELECTION WITH CHI-SQUARE INDEPENDENCE TEST - Ilham Darussalam; Evi WIjayawati; M. Syahrie Khamdani; Fitriana Nur Afifa (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Tadulako, 2025)
General elections in Indonesia are crucial for democracy, enabling citizens to directly choose their leaders. But the abstention or the